Description of the final stadium larva of Anisopleura furcata Selys, 1891 (Odonata: Euphaeidae) from Thailand - Keetapithchayakul, Tosaphol Saetung; Orr, Albert G.; Wongkamhaeng, Koraon (Zootaxa, 2024)
The final stadium larva of Anisopleura furcata Selys, 1891 is described and illustrated. The larva can be separated from all known Anisopleura Selys, 1853 larvae by the following characters: the profusion of elongated tubercles on the labrum and antefrons, the presence of a long bifid spur on the outer margin of the mandibles, presence of a row of claviform setae on dorsal apex of tarsus, and antennae 8-segmented. The inner lobe of the labial palps forms a tiny truncate tooth broadly similar to the condition in all other known members of the genus. Diagnostic features that separate this species from potentially syntopic euphaeid genera are discussed.